Sosialisasi Peningkatan Gerakan 1 Rumah 1 Jumatik Untuk Pengendalian Demam Berdarah Dengue - Mufidah, Hartalina; Agustin, Ayu Tri; Wijaya, Anas Fadli; Muflihah, Ahdiah Imroatul (Yayasan Inspirasi El Burhani, 2025)
Introduction: Dengue Hemorrhagic Fever remains a significant health problem in Jember Regency. Jember Regency is among the top three districts with the highest dengue cases in East Java, reporting 781 cases, alongside Malang Regency was 1,224 cases and Ngawi Regency was 673 cases. It situation may be attributed to the lack of public awareness about maintaining a mosquito-free environment and the suboptimal implementation of the